PENERAPAN FUZZY LOGIC DAN LCG DALAM GAME QUIZ UNTUK PEMBELAJARAN COVID - Octavianus, Jaeson; Setiawan, Rendy; Hakim, Lukman (LPPM UNIKA Santo Thomas, 2022)
The Corona Virus 19 pandemic or Coronavirus Disease 19 (COVID19) is a disease caused by a corona virus that usually attacks the respiratory tract. Covid-19 disease can be transmitted when a person show symptoms such as fever, runny nose, cough, throat, and headache; although many cases occur without any symptoms (Rothan, 2020). Covid-19 cases in Indonesia continue to increase every day based on data from Deti Mega Purnamasari in kompas.com, where until April 15, 2020 there were 5,136 positive cases of Covid-19. This research will produce a game where players will be able to learn while playing quizzes to increase their knowledge about the symptoms and ways to prevent the occurrence of covid. To study covid, information that can be used as a benchmark is needed to be used as questions in the game. Fuzzy is used to give a score that will increase every time you answer correctly and LCG (Linear Congruential Generator) is used to give random questions to players. Based on the experiment done, only 50% of 10 people have sufficient knowledge about covid19 daily. By making this game, public awareness about covid will increase.